2007
DOI: 10.1590/s0104-71832007000100011
|View full text |Cite
|
Sign up to set email alerts
|

O ensino religioso e a interpretação da lei

Abstract: O trabalho trata das diferentes interpretações da Lei de Diretrizes e Bases da Educação, de 1996, especialmente da reformulação de seu artigo 33, de 1997, que implementou e regulou o ensino religioso em escolas públicas. Sendo essa regulamentação referente aos ensinos de primeiro e segundo graus, ficou a cargo dos diferentes estados por em prática os ditames legais, através de suas Secretarias de Educação. Vamos considerar dois casos específicos, o de São Paulo e o de Santa Catarina, mostrando como essas difer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 2 publications
(1 reference statement)
0
8
0
3
Order By: Relevance
“…Protestants were divided into two groups: one that insisted on the defense of the laic school and another which allied itself with the Catholics and demanded to be present in school curricula. The inclusion of religious education in the new, democratic Constitution was largely made possible by a Christian lobby, especially that of the Catholic Church, beginning with the constituent process of 1987/1988Lui, 2007;Cunha, 2014).…”
Section: Religious Educationmentioning
confidence: 99%
See 4 more Smart Citations
“…Protestants were divided into two groups: one that insisted on the defense of the laic school and another which allied itself with the Catholics and demanded to be present in school curricula. The inclusion of religious education in the new, democratic Constitution was largely made possible by a Christian lobby, especially that of the Catholic Church, beginning with the constituent process of 1987/1988Lui, 2007;Cunha, 2014).…”
Section: Religious Educationmentioning
confidence: 99%
“…In the first alternative, religious teachers or advisors would be trained or accredited by the respective religious organizations. According to Cunha (2014), that language ("with no onus to the State budget") did not last long, as, in the ceremony in which the bill was signed into law, president Fernando Henrique Cardoso himself suggested that the prohibition against paying religious education teachers be 3 "This lobby took place beginning with the National Constituent Assembly period, when organizations such as the Curitiba Interfaith Education Association (ASSINTEC, in Portuguese), from Paraná, the Council of Churches for Religious Education (CIER, in Portuguese), from Santa Catarina, the Pastoral Institute of Campo Grande, Mato Grosso (IRPAMAT, in Portuguese) and the CNBB Education Sector, especially the National Reflection Group on Religious Education (GRERE) took over negotiations, legitimated by state coordinators of religious education from states where it was already regulated" (Dickie;Lui, 2007:239). Later, the National Council of Christian Churches (CONIC, in Portuguese) joined this group.…”
mentioning
confidence: 99%
See 3 more Smart Citations